Exploring Factors Influencing Students' Satisfaction at Arked Meranti, Universiti Teknologi Malaysia - Khazainah Khalid; Nor Salwani Sumantry; Nurul Diana Syahira Abu Bakar; Jazira Anuar; Mushaireen Musa (Information Management and Business Review, 2025)
Student satisfaction with campus food services plays a crucial role in their well-being and academic success. This study explores the key food service attributes influencing student satisfaction at Arked Meranti Cafeteria, Universiti Teknologi Malaysia, Skudai, Johor, focusing on students from Rahman Putra College and Tun Fatimah College. A quantitative research design was employed, with data collected from 341 students through an online survey distributed via Google Forms. The survey covered demographic details and four key food service attributes: food and beverage quality, service quality, setting quality, and price-value perception. Data was analyzed using IBM SPSS Statistics version 27. The results indicate that all variables significantly contribute to overall student satisfaction. Descriptive analysis provided insights into satisfaction levels, while multiple regression analysis determined the relative impact of each attribute. The findings reveal that setting quality (? = 0.331) has the strongest influence on satisfaction, followed by service quality (? = 0.316) and food and beverage quality (? = 0.219), whereas price and value (? = 0.005) have the least impact. These findings expand existing knowledge on student satisfaction at Arked Meranti by emphasizing the significance of key factors. Additionally, they offer recommendations for university management to improve student satisfaction.